Tracking Activities for Data Verification of Motorized Vehicles Not Re-Gisterin in Bekasi City, West Java, Indonesia - Dwikora Harjo (Yayasan Ilomata, 2021)
This research was conducted to determine the level of effectiveness of tracing implementation activities in order to verify the accuracy of data on motorized vehicles that did not re-register in an effort to support the regional tax stimulus policy provided by the Regional Revenue Agency of West Java Province in the face of the COVID-19 pandemic in Bekasi City. This study uses a qualitative approach and descriptive research type by conducting library research and data collection using documentation on data obtained from related agencies. The results show that the West Java Provincial Government through the Regional Revenue Agency of West Java Province in an effort to relieve Motor Vehicle Taxpayers affected by the Covid-19 pandemic in 2020 has provided a Motor Vehicle Tax stimulus, including exemption from Motor Vehicle Tax fines and giving discounts in tax payments. Motorized Vehicles and Motor Vehicle Title Fee, provided that all data are validated. So that the public can enjoy the stimulus, the West Java Bapenda collaborates with various parties to conduct verification and validation of Motor Vehicle Taxpayer data with the level of the effectiveness ratio of these activities in 2020 of 77.01%, a decrease compared to the achievement in 2019 of 89.09% and in 2018 amounted to 82.14%.